Maternal factors associated with stunting among children under two years in South Nias, Indonesia: a cross-sectional study - Purba, Ivan Elisabeth; Tarigan, Yenni Gustiani; Zendrato, Arisman; Purba, Agnes; Sinaga, Taruli (Intelektual Pustaka Media Utama, 2024)
The Indonesian Nutritional Status Survey 2022 reported that the prevalence of stunted children in South Nias, a district in North Sumatera, was 27.2%, higher than the regional and national prevalence of stunting. Stunting can be caused by many factors including maternal nutritional status, exclusive breastfeeding, and inadequate food intake. This research aims is to analyze the relationship between maternal factors and cases of stunting in children under two years at Somambawa Community Health Center, South Nias Regency. It was a quantitative study with a cross sectional design. Using a total sampling technique, 72 mothers with children under two years were included in the study. Exact fisher statistical and logical regression tests were carried out in bivariate and multivariate analyses. This study found that there was a significant relationship between antenatal care visits (p-value=0.000) and exclusive breastfeeding (p-value=0.000) with stunting in children under two years old. Exclusive breastfeeding was the most dominant predictor of stunting in the study, namely 84 times (p-value=0.000; OR 84.00). Meanwhile, complementary feeding and knowledge did not show a significant relationship with stunting. Therefore, health education to provide information and knowledge about stunting, especially about exclusive breastfeeding and complementary food for babies is suggested.